Performance Analysis of Wireless Local Area Network Using Router Tenda N-300 - Catur Budi Waluyo; Alber Erik; Yenni Astuti (Compiler, 2019)
Today's wireless communication system is a trend for the information society. This is inseparable from communication needs with high mobility and low costs. One of them is the Wireless Local Area network with the IEEE 802.11 standard. Wireless LAN is a communication technology that uses radio wave transmission media by utilizing free space as a transmission line. The transmitted signal is strongly influenced by distance, frequency, transmitter power, receiver sensitivity, and antenna gain. A loss occurs in the process of transmitting data from the sender to the recipien. In order to no loss that occurs, it requires a good performance, and a wide coverage area. The purpose of this study is to analyze the QoS data, calculate the coverage area, receiver power, and compare the results of theoretical calculations with the measurement results. The analysis results show the average throughput for each data rate of 6 Mbps, 15 Mbps and 35 Mbps at 383.8 kbps, 328.2 kbps and 329.8 kbps. The average delay is 5.28 ms, 4.81 ms and 4.66 ms. The average packet loss is 2.83% ms, 2.66% ms and 2.16% ms. The average jitter is 0.036 ms, 0.032 ms and 0.014 ms.